Exploring the Tradition of 'Pamantang': Prohibitions and Beliefs Surrounding Pre-Marriage Practices in the Banjar Society - Fithriani, Ahda; Rahim, Niska Kamalia (Interdisciplinary Explorations in Research Journal, 2024)
Abstract In the Banjar society, prohibitions or restrictions are referred to as "pamantang," encompassing beliefs rooted in religion, culture, and local customs. In the present era, a significant number of Banjar people still believe that adverse events may occur if these prohibitions are not adhered to. One such restriction is refraining from leaving the house before the marriage ceremony (akad nikah) takes place, as it is believed to have negative consequences if not followed, potentially leading to misfortune (bala). Using a qualitative method and analyzed with a sociological and phenomenological approach, the tradition of refraining from leaving the house for prospective brides and grooms in the Banjar community can be explored. In Banjar society, these prohibitions are deeply intertwined with religious beliefs, cultural norms, and local traditions. Qualitative analysis, employing sociological and phenomenological lenses, aims to delve into the subjective experiences and meanings attached to these traditions. It is noteworthy that in the Banjar community, these prohibitions, also known as "pamantang," continue to be practiced and believed in until today, with the aim of future well-being. Importantly, these practices are not in conflict with Islamic values. In-depth qualitative analysis, involving active participation in the community and open dialogue with its members, will be instrumental in comprehending the complexity and persistence of these traditions in contemporary times. Keywords: Tradition, Taboo, Future Bride And Groom Abstrak Dalam masyarakat Banjar, larangan atau pembatasan dikenal sebagai "pamantang," mencakup keyakinan yang berakar dalam agama, budaya, dan adat istiadat lokal. Pada era saat ini, sebagian besar masyarakat Banjar masih meyakini bahwa peristiwa buruk dapat terjadi jika larangan ini tidak diikuti. Salah satu larangan tersebut adalah untuk tidak meninggalkan rumah sebelum upacara pernikahan (akad nikah) berlangsung, karena diyakini dapat menyebabkan konsekuensi negatif dan potensi ketidakberuntungan (bala) jika tidak diikuti. Dengan menggunakan metode kualitatif dan dianalisis dengan pendekatan sosiologis dan fenomenologis, tradisi ini dapat dijelajahi lebih lanjut di komunitas Banjar. Dalam masyarakat Banjar, larangan ini erat terkait dengan keyakinan agama, norma budaya, dan tradisi lokal. Analisis kualitatif dengan lensa sosiologis dan fenomenologis bertujuan untuk menyelami pengalaman subjektif dan makna yang melekat pada tradisi ini. Perlu dicatat bahwa di komunitas Banjar, larangan ini, yang dikenal sebagai "pamantang," terus diamalkan dan diyakini hingga saat ini, dengan tujuan kesejahteraan di masa depan. Penting untuk dicatat bahwa praktik-praktik ini tidak bertentangan dengan nilai-nilai Islam. Analisis kualitatif mendalam, melibatkan partisipasi aktif dalam komunitas dan dialog terbuka dengan anggotanya, akan menjadi kunci untuk memahami kompleksitas dan ketahanan tradisi ini dalam konteks zaman kontemporer. Kata Kunci: Tradisi, Larangan, Calon Pengantin